Detection of Cloud Top Height, Cloud Base, Cloud Height and Cloud Temperature Using Ka-Band Radar Data - S. Tandale, Nikita; Gaikwad, S.V (International Journal of Computer Sciences and Engineering, 2020)
This paper presents a cloud detection based framework for addressing the problem of accurate cloud detection using Ka-band scanning polarimetric radar (Ka-SPR). This framework benefits from Python , which is capable of pixel level labeling of cloud regions and also for identification approach is proposed to identify Cloud Height(CTH), Cloud Base(CB), Cloud Top(CT) and Cloud Temperature (CTemp). Cloud properties detection is an important application of science and technology to detect clouds and measure the amount of water content over a region. The detection is based on various data collection means. Some most recent techniques for weather data collection are based on graphical data from satellite, sensor data collected from different areas, the radar data for cloud parameters, rain gauge which major liquid precipitation for a specific period and disdrometer data which gives drop size distribution. Correlation of CTH, CT, CB is used for calculating reasonable estimation of these parameters. Estimates may also improved somewhat by an observation of cloud types. By using CT data and Cloud pressure the estimation of CTemp is carried out. Different constants were derived from the microscopic properties correlation consistent with each respective cloud type.